2009
DOI: 10.1017/s1368980008003170
|View full text |Cite
|
Sign up to set email alerts
|

Increased knowledge predicts greater adherence to the Mediterranean diet in Greek adolescents

Abstract: Objectives: To examine knowledge of and adherence to the Mediterranean dietary pattern (MDP) among Greek adolescents, assess associations between MDP knowledge and adherence with BMI, and determine socio-cultural factors predicting MDP compliance. Design: Cross-sectional. Setting: Greek adolescents aged 15-17 years. Subjects: Two hundred adolescents (103 females, ninety-seven males) from six schools on the Greek island of Chios. The sampling procedure was similar for all schools; schools were randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 47 publications
1
28
0
1
Order By: Relevance
“…Table 1 provides a summary of each study included for the review. The studies were published between 1993 and 2013 and included ten cross-sectional studies (5,(35)(36)(37)(38)(39)(40)(41)(42)(43) , two intervention studies (44,45) and one longitudinal cohort study (9) . One of the cross-sectional studies (38) was a part of the longitudinal cohort study (9) .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 provides a summary of each study included for the review. The studies were published between 1993 and 2013 and included ten cross-sectional studies (5,(35)(36)(37)(38)(39)(40)(41)(42)(43) , two intervention studies (44,45) and one longitudinal cohort study (9) . One of the cross-sectional studies (38) was a part of the longitudinal cohort study (9) .…”
Section: Resultsmentioning
confidence: 99%
“…While some studies observed an inverse association between the Mediterranean dietary pattern and BMI [33, 37, 38], others found no relationship between BMI and the KIDMED index [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies from the United States (11)(12)(13) and Europe (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) indicate that the diets of many university students (14)(15)(16)(17)(18)(19)(20)(21) and adolescents (22)(23)(24) do not conform to dietary recommendations, which may place these groups at increased risk of obesity and chronic disease (25). Knowledge of a healthy diet is one of the most important determinants of food choice (26) and predicts adherence to a healthy diet in adolescents (23,26). If knowledge does indeed predict intake, then university students enrolled in nutrition courses-who presumably have increased knowledge of dietary choices and their implications-would be anticipated to have diets healthier than those of the general Canadian population.…”
Section: Discussionmentioning
confidence: 99%